Reproductive health needs of female sex workers and opportunities for enhanced prevention of mother-to-child transmission efforts in sub-Saharan Africa. Issue 1 (25th November 2015) - Schwartz, Sheree R; Papworth, Erin; Ky-Zerbo, Odette; Sithole, Bhekie; Anato, Simplice; Grosso, Ashley; Ouedraogo, Henri Gautier; Tchalla, Jules; Ntshangase, Cebisile; Ketende, Sosthenes; Baral, Stefan
Abstract : Introduction: HIV infection and pregnancy are both common among female sex workers (FSW), indicating the need for prevention of mother-to-child transmission (PMTCT) among FSW. Methods: FSW were enrolled into studies in Swaziland, Burkina Faso and Togo using respondent-driven sampling. Women completed interview-administered socio-behavioural surveys and HIV counselling and testing. This secondary analysis describes contraceptive use and attempted pregnancy among reproductive-aged FSW (16–49 years). Robust Poisson regression with generalised estimating equations to account for clustering within recruitment networks was used to separately estimate associations between current unmet contraceptive need and attempted pregnancy among FSW. Results: Overall 1666 FSW were enrolled, 1372 (82.4%) of whom had ever been pregnant. In Togo and Burkina Faso, 83 FSW reported a prior HIV diagnosis and having a child, of which 12.1% (10/83) reported a child known to be HIV-positive. Twenty-five per cent of FSW had an unmet need for contraception; 9% of FSW employed dual contraception, including highly effective non-barrier methods and consistent condom use. Consistent condom use varied substantially by partner type and was higher with clients than non-paying partners. Nineteen per cent ( n =313/1666) of FSW were trying to conceive. HIV-positive, undiagnosed FSW were more likely to be trying to conceive as compared to HIV-negative FSW; among 98 HIV-positive women trying to conceive, 25.5% were on antiretroviral therapy. Conclusions: FSW have varying reproductive goals and contraceptive usage. Efforts to improve coverage of comprehensive family planning – including efforts to increase HIV testing and engagement in treatment among FSW trying to conceive – are necessary for PMTCT.